ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENABUNG MASYARAKAT PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG BANGKALAN - Dewi Sharaswati; Crisanty Sutristyaningtyas Titik; Henny Oktavianti (MediaTrend, 2013)
The purpose of this research is to analyze the influence of the independent variable in the partial (singly) against interest saving society and to know the most dominat influence the interest saving society in Bangkalan. The data are used in the research is the primary data obtained from the dissemination of questionnaires to consumers who become the respondent as well as secondary data obtained from BI (Bank Indonesia) and the central statistical office Bangkalan. Data tested reliability and validity, the method used in this research is quantitative analysis method of ologit (Ordered Logit) using STATA 10. Significant variables that influence is income variable, gift, age and reputation of banks, while no effect significant variables is interest rest, facilities, security and education. Variables that have a dominant influence on the interest saving society is a income variable.